Another bloody century future warfare - Gray, Colin S. (Phoenix, 2005)
Colin S. Gray has advised governments on both sides of the Atlantic about military affairs, and he looks into the future to provide some intriguing answers about the ways Western armed forces-which have traditionally been trained to fight conventional, not guerrilla, warfare-may have to evolve.